Enhanced graphical user interface (GUI) for autonomous agricultural vehicle - Mohd Kassim, Muhamad Saufi; Wan Ismail, Wan Ishak (2005)
An autonomous tractor was developed in 2003. Automatic controls of the tractor rely on the developed GUI. Which through the GUI user monitor the tractor’s sensor data and observe the movement of the tractor through the simulation window on the GUI.Enhanced GUI, incorporated visual information to support the oil palm harvesting operation. An hydrostatic transmission Kubota tractor was modified and converted to an autonomous tractor. The automated system of the tractor rely on the use of GUI. Through the GUI, user enable to monitor the tractor the sensor data and observe the movement of the tractor through the simulation window. Enhanced GUI was developed to incorporate the visual information for the purpose of oil palm harvesting and weed spraying operationThe visual information was useful for the operator to view the location of the oil palm and positioning the mechanical harvester. A software module was also developed for spraying operation. In the spraying software module the visual information was processed to determine the weeds density and weeds location. The controller will decide on the amount of herbicide mixture and select the respective nozzle. A client – server application was developed to enable automatic control through the wireless network. A better tractor movement simulation was also developed to incorporate the virtual joystick.